Annual Plan Proposals 2012-13 Government of Kerala - Planning Commission (Planning Commission, 2012)
The Twelfth Five Year Plan provides an opportunity to consolidate the gains that have been made in the previous plans and also to correct the deficiencies that have been observed. Much higher levels of agricultural development can be achieved through a reorientation of the planning approach and existing technologies with improved delivery systems. Most of the gains in 12th plan will have to come by exploiting the potential of existing technology.
State Planning Board Thiruvananthapuram